Senderización y señalética turística del atractivo natural Cerro Arqueológico Putushio, de la Parroquia Rural el Tablón Cantón Saraguro de la Provincia de Loja - CHUQUIMARCA SOTO, JOSÉ LUIS (2018)
The Tourism focuses on the economic development of our country, for conserving great natural and cultural wealth together with its attractions, traditions, customs, gastronomy among others being one of the main factors in the generation of employment to the inhabitants. Ecuador has four regions: Costa, Sierra, Oriente and the Insular Region. One of them is the Sierra Region, characterized by its impressive mountainous elevations, volcanoes and snow-capped mountains. There are also several national parks with very rich and varied flora and fauna. Within this region we can find the province of Loja that has sixteen cantons, such as the Saraguro canton that is part of the province of Loja, is located 67 kilometers, as all cantons has an infinity of attractions And tourism resources, concentrated in each of its parishes, such as the rural parish El Tablón located 22 kilometers from the cantonal head of Saraguro via the province of Azuay, the aforementioned parish belongs to the Saraguro Canton. As for the political division of the Tablón parish, it is divided into the following rural districts: San José, Tablón Viejo, Apuguín and the urban center of Tablón. The the Board parish holds a lot of history and culture, since the beginning of humanity for being the birthplace of the Putushio and Jubilan cultures dating from 10,000 to 8,000 years BC, whose remains have been studied for a long time by the German Scientific name Matilde Thome. The parish bulletin is a power in tourism for the wealth of natural attractions, yet could not be used by the people or by tourists visiting the parish, either by several factors such as: ignorance, promotion and enhancement of The natural tourist attractions. To this great inconvenience is added the lack of tourist trail and signage to the natural attractions of the parish, causing a low index in the economic, cultural and tourist development of this place. The present research work seeks to improve the tourist activity of the parish, it is for this reason that it has been convenient to carry out the following project called "SENDERIZATION AND SIGNALISTIC TOURISM OF THE NATURAL ATTRACTIVE CERRO ARCHEOLOGICAL PUTUSHIO OF THE RURAL PARISH EL TABLÓN CANTÓN SARAGURO, PROVINCE OF STORE "whose purpose is the conservation and protection of natural attractions, the subject in reference has been at present of great interest, by the community of this sector especially by the Authorities of the parochial GAD. Cerro Putushio is located in the province of Loja in the Saraguro canton of the rural parish of Tablón, being a very important place for its population due to the great tourist value that it possesses, in this way it aims to make known and provide a Contribution to the tourist development of the Parish, ensure and guarantee that the constitutional precepts of the Good Living of the inhabitants are fulfilled. 5 The present thesis had as general objective: To develop the Senderización and tourist signage of the natural attraction Cerro Archaeological Putushio of the Rural Parish El Tablón Saraguro Canton, Province of Loja. Y With the following specific objectives: To carry out the Tourist Diagnosis of the current situation of the Rural Parish El Tablón; To propose the Senderization and Tourist Signal of the natural attraction Cerro Arqueológico Putushio of the parish El Tablón, Saraguro canton of the Province of Loja; And finally Identify the significant environmental impacts generated in the project stages. The methodology was developed based on the fulfillment of each one of the objectives proposed with different methods and techniques; In the first objective secondary sources such as the bibliographical collection and the primary sources like direct observation, field research and interviews were used. Together, Carla Ricaurte's tourism characterization matrix was adjusted according to the reality of the parish. She also worked with the MINTUR Tourist Attraction Inventory Tokens and the FODA Matrix. As for the second objective was carried out the information gathering for it was used some tools such as the use of GPS, which allowed pick up points and coordinates for the design of the maps of the trail; To determine the carrying capacity was carried out under the methodology of the author Miguel Cifuentes; As far as the signage is designed strictly of the Manual of Tourist Signage of the Ministry of Tourism. Finally, in order to meet the third objective, Leopold 's cause - effect matrix was applied to see the impacts that would result from the execution of the project. In conclusion the parish El Tablón has a great variety of important tourist attractions to promote tourism development, the same ones that need to be adequate and potentialized by the relevant authorities. It is worth mentioning that this site lacks signs that allow the tourist to guide themselves correctly, with this proposal of senderización and tourist signage will positively contribute to the attraction and its visitors, since with this it will contribute to the protection and conservation of the same, at the same time Will offer relaxation, comfort and security to the visitor at the time of carrying out the tourist activity. For this reason it is recommended mainly to the GAD of the parish, that through agreements with MINTUR carry out projects that are related in the tourist field.